Terapi Wicara Dalam Mengembangkan Kemampuan Komunikasi Anak Disabilitas Di SLB Negeri 2 Yogyakarta - Sholehah, Siti Hidayatus; Nurjannah, Nurjannah (Jurnal Ilmu Bimbingan dan Konseling, 2026)
Developing the communication skills of children with disabilities is crucial to support academic skills and communication interactions. These communication skills can be developed through specific and intensive teaching and training, one of which is speech therapy. Speech therapy itself is an effort to assist children in improving their communication skills through various exercises. Speech therapy conducted at SLB Negeri 2 Yogyakarta includes three stages: the initial stage, which includes room preparation, child preparation, and reward preparation; the second stage, which involves eye contact, instructions, responses, prompts, and rewards; and the third stage, which involves recording the child's progress in a child development notebook and evaluating it weekly. Evaluation results indicate that speech therapy significantly assists in developing the communication skills of children with disabilities. Previously, children had difficulty pronouncing words, responding to instructions, and communicating with their surroundings. However, after undergoing speech therapy, children began to pronounce words more clearly, respond to instructions, and showed improvement in communicating with teachers and peers.